From the state of exception to the authority state: the control of the written press media. the case "diarios chicha" in Peru - Alarcón Requejo, Gilmer (2018)
Based on the review of the judicial reasoning on the “Diarios Chicha” case, both in the conviction and in the acquittal of former president Alberto Fujimori, the relevance of the context of the State of exception is analyzed, in which they were developed facts of an authoritarian state. It is postulated that the lack of an analysis and assessment of the context of discovery and of the conceptual elements on the State of exception, facilitated the acquittal of the former president of the use of public treasury money for the purchase of editorial lines of the written press in his eagerness for a second reelection.